Phytochemical, antibacterial and cytotoxic properties of piper betle L. (Bangladesh Journal of Botany, 2024)
The phytochemical, antibacterial and cytotoxic characteristics of Piper betle L., leaf extract was examined. The phytochemical analysis revealed the presence of glycosides, alkaloids, terpenoids, flavonoids, tannins, and saponins. The presence of different phytochemicals will help in anticipating their pharmacological action in searching for bioactive agents. Antibacterial effects were evaluated against six bacterial strains. The tested extract exhibited no antibacterial action against any bacterial strains investigated. Cytotoxicity was assessed on HeLa and Vero cell lines employing the Cell Counting Kit-8 test. The methanolic extract exhibited cytotoxicity against HeLa and Vero cells with an IC50 value of 270 μg/ml and 240 μg/ml, respectively.  This preliminary investigation highlights the promising anticancer activities of P. betle leaf extract in vitro, suggesting its potential for developing novel anticancer agents. However, cytotoxicity towards Vero cells raises concern for fundamental research in drug discovery and regulatory decision-making, thereby shaping the course of subsequent studies and applications.Bangladesh J. Bot. 53(4): 889-894, 2024 (December)